Development of Project-Based Authentic Assessment Instruments On Business Communication Subjects - Indah Putri Arlinawati; Agus Hermawan (JPBM (Jurnal Pendidikan Bisnis dan Manajemen), 2017)
he goal of this research and development was to produce authentic assessment instrument based project to ease teachers conducting assessment authentically to the process and student learning outcome in making brochure towards business communication subject.This research was research development which used R &D model. Data collection instrument in this research conducted through questionnaire. Data type that obtained in this research was quantitative data and qualitative data by using data analysis technique of percentage calculation. The result of limited test showed that this authentic assessment instrument based project had percentage of 97% with “easy to use” criteria, while readability test to the work instruction sheets had the average of 95% with “feasible to be used” criteria.